Pancytopenia: A multidisciplinary assessment of hemato-etiological and clinical spectrum in a tertiary care hospital - Dr. Trupti Vyasrao Katti; Dr. Anand Anantharao Shankar; Dr. Tejeshwini Patil; Dr. Sangeeta Seshagiri K. (Tropical Journal of Pathology and Microbiology, 2018)
Background: The causes of pancytopenia range from simple, completely treatable diseases to serious life-threatening conditions. A thorough evaluation of these cases is mandatory as it would benefit the patients to receive appropriate treatment. Objectives: Evaluation of etio-hematological and clinical spectrum of pancytopenia. Settings and Design: A prospective study of two years (Jan 2016 -December 2017) was conducted on pancytopenic patients, attending Navodaya Medical College, Hospital and Research Centre, Raichur, Karnataka. Material and Methods: Etio- hematological and clinical evaluation was done considering the relevant biochemical and serological investigations. Results: A total number of 1368 cases were diagnosed as pancytopenia. The patients’ age ranged from 19 to 68 years and M: F ratio was 2.1:1. Most frequent clinical symptom was generalized weakness (90%) and least was bony pain (2%). Peripheral smear examination revealed predominantly macrocytic blood picture (47.9%). Bone marrow aspiration was performed in 444 cases (32.4%), among which Megaloblastic anaemia (Exclusive and Combined with iron deficiency anemia) was the commonest (52.7%). Etiologies of pancytopenia in decreasing order of frequency included Megaloblastic anemia 935 cases (68.4%) – Exclusive type (713 cases; 52.2%) and Combined with iron deficiency anemia (222 cases ;16.2%), followed by Dengue fever (141 cases ;10.3%), Hypoplastic/Aplastic anemia [106 cases ;7.8% (Drug induced - 4 cases; 0.2%)], Septicemia (60 cases ;4.5%), Leukemia (46 cases ;3.25%), Chronic malaria (46 cases ;3.25%) and Myelodysplastic syndrome (34 cases; 2.5%). Conclusion: Keeping in mind varied etiologies of pancytopenia, thorough diagnostic evaluation is required to achieve better clinical outcome.